Designing of Service Dominant Logic and Business Model Canvas: Narrative Study of Village Tourism - Mariana Simanjuntak (Manunggal Halim Jaya, 2021)
The purpose of this research is to design service design, design a canvas business model (BMC) based on the design of services that have been designed and know the role of society. The required data is divided into two, namely primary data and secondary data. Primary data was obtained by conducting interviews and observations to tourists, managers and the community around Siregar Aek Nalas. Primary data obtained such as access, amenities, safety and security, processes, physical or digital artifacts, stakeholders/stakeholders, and Village Tourism services. Secondary data is obtained by conducting literature studies. The strategy carried out to develop Siregar Aek Nalas is the design of Service Dominant Logic (SDL) by creating a map of tourist travel before the visit, during the visit and the completion of the visit from the primary data obtained then carried out the design of the canvas model business with the presence of nine components customer segment, value proposition, channel, customer relationship, revenue stream, key of resource, key of activities, key of partnership and cost structure. Service Design is done by co-creation of tourist travel map before visit, during visit and completion of visit. The creation of a tourist travel map is based on eight programs.